SOSIALISASI PERANCANGAN SIA PERSEDIAAN BARANG BERBASIS DIGITAL BUSINESS PADA CV ISTANA KOMPUTER - Sa’adah, Nur Halimatus; Armaini, Rosy; Hartati, Sri; Widyastuti, Endah (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2025)
CV Istana is a business entity engaged in the sale of computer goods, printers, and computer accessories. Inventory recording is still done manually in this business. The problem that may arise in the business entity is having difficulty when recapitulating, resulting in the physical amount not being in accordance with the amount on the transaction evidence. System development using the warterfall method to produce purchase journals, sales, general journals, ledgers, inventory cards, and profit and loss reports. With this application, it can be presented effectively, efficiently, and accurately so as to help companies in knowing sales data, purchases, and available stock of goods and improving internal control.